Evaluation of the basic surface roughness of an ISO-certified and non-ISO-certified slot bracket with an atomic force microscope - Jusup, Chrisni Oktavia; Soemantri, Eky Setiawan Soeria; Mardiati, Endah; Evangelina, Ida Ayu (Padjadjaran Journal of Dentistry, 2019)
Introduction: The base surface roughness of slot bracket can affect friction in tooth movement. There are ISO-certified and non-ISO-certified stainless steel brackets on the market. Thus orthodontists must be careful in choosing the right bracket. This study was aimed to evaluate the differences of the surface roughness of ISO-certified and non-ISO-certified Roth 0.022 inch stainless steel bracket with the parameter of S a (average roughness). Methods: This research was a laboratory observational. Samples were taken randomly as many as 32 brackets divided into two groups, each consisted of two bracket brands. Surface roughness measurements were performed using an atomic force microscope (AFM), then the data were analysed by ANOVA test (p < 0.05) and Post-Hoc analysis. Results: The ISO-certified bracket has an S a value smaller than the non-ISO-certified bracket. There was a significant difference in the surface roughness of the ISO-certified and non-ISO-certified slot bracket base (p < 0.05). Conclusion: The ISO-certified bracket has a smoother base surface than the non-ISO-certified bracket base.Keywords: Surface roughness, stainless steel slot bracket, atomic force microscope